On the 75th birth anniversary of Marat Mirzaevich Arslanov - I.Sh. Kalimullin; V.L. Selivanov (Учёные записки Казанского университета: Серия Физико-математические науки)
The paper describes the biography and the main scientific achievements of Marat Mirzaevich Arslanov, the Head of the Department of Algebra and Mathematical Logic of Kazan Federal University, Professor, who is the founder of the Kazan School of Mathematical Logic and Computability Theory.